Teachers Can Be Financially Fit Economists$1 (BAdvice for Educators /s - Hunt Ferrarini, Tawni; Niederjohn, M. Scott; Schug, Mark C.; Wood, William C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book uses relatable case studies to dispense practical financial advice to educators. Written by an expert team of four award-winning economics educators, the book provides an engaging narrative specifically designed for teachers and their unique financial needs. Educators are attracted to the teaching profession for numerous reasons. Prospective teachers enter the profession believing it offers a certain level of job security and good benefits, usually including a defined-benefit, state-funded pension. But things are changing. Pensions vary widely from state to state and even within school districts. Many private schools do not offer even basic 403(b) saving plans and, when they do, they are often not very generous. Much the same can be said of many charter schools and private colleges and universities. The book consists of fourteen chapters covering a comprehensive group of topics specifically curated for educators teaching at the K-12 and university level, including saving for retirement, managing debt, investment strategies, and real estate. Each chapter begins with a case study of an educator in a specific financial situation, which sets the scene for the introduction and explanation of key concepts. The chapters include a Q&A section to address common questions and conclude with a (3z(BFinancial 911(3y (Bfocusing on a financial emergency related to the chapter topic.s
Chapter 1: Yes, Teachers Can Be Financially Fit -- Chapter 2: Spending and Saving: A Guide for Teachers -- Chapter 3: Earning Extra Income -- Chapter 4: Teachers$1 (BWheels: Cars and Transportation -- Chapter 5: Walls and a Roof: Housing for Teachers -- Chapter 6: Managing Credit and Debt -- Chapter 7: Investment Basics for Teachers -- Chapter 8: Retirement for Public School Teachers -- Chapter 9: Saving for Retirement: Options for Charter and Private School Teachers -- Chapter 10: The Higher Education Connection -- Chapter 11: Educators and Insurance -- Chapter 12: Unconventional Risk Management -- Chapter 13: Teachers in a Market Economy -- Chapter 14. Don$1 (Bt Keep It a Secret.s
Keywords: Personal finance; Pension plans; Risk management; Finance; Economics; Teaching; Personal Finance/Wealth Management/Pension Planning; Risk Management; Popular Science in Finance; Popular Science in Economics; Teaching and Teacher Education